Examining DIR/Floortime™ as a Treatment for Children With Autism Spectrum Disorders: A Review of Research and Theory. (September 2017) - Mercer, Jean
Purpose: To review and assess theory and research supporting DIR/Floortime™, a method proposed for treatment of young children with autism spectrum disorders (ASD). Methods: Published materials describing the principles of DIR/Floortime™ were evaluated. Published outcome research articles were assessed for the adequacy of their design and implementation and the extent to which their conclusions were supported. Results: The theoretical basis of DIR/Floortime™ appears to be generally plausible. Of the 10 outcome research articles in print, all concluding that DIR™ effectively treated ASD, five provided a comparison group, or used a randomized design, or did both. These studies failed to equalize the duration and frequency of DIR™ and the comparison treatment. Conclusions: DIR™ can be considered by social work practitioners as a possibility for evidence-based practice (EBP), but not as an evidence-based treatment (EBT). Further outcome research needs to concentrate not only on randomized design but on other design issues.